Functional materials
Patent Information
- Application Number
- JP2023100522
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-08
AI Technical Summary
【0007】 本発明の機能性材料におけるパルプは、そのセルロースの水酸基の少なくとも一部が硫酸エステル基で置換されていることで、無機多孔結晶等を介することなく、アルカリ金属イオン以外の金属イオンを担持可能である。
Smart Images

Figure 2025001116000001 
Figure 2025001116000002 
Figure 2025001116000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a functional material. [Background technology]
[0002] A functional material has been proposed in which inorganic porous crystals such as zeolite are contained within a hydrophilic polymer such as wood-derived pulp, and metal ions are supported on the inorganic porous crystals (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4149066 Summary of the Invention [Problem to be solved by the invention]
[0004] As described above, the functional material described in Patent Document 1 is one in which metal ions are supported on inorganic porous crystals inside pulp, etc. In contrast, it would be convenient if metal ions could be supported directly on pulp without going through inorganic porous crystals.
[0005] Therefore, an object of the present invention is to provide a functional material containing pulp that supports metal ions other than alkali metal ions without the intervention of inorganic porous crystals or the like. [Means for solving the problem]
[0006] In order to achieve the above object, the functional material of the present invention comprises: The present invention includes a metal ion-supported pulp in which metal ions other than alkali metal ions are supported on a pulp in which at least a portion of the hydroxyl groups of cellulose are substituted with sulfate ester groups (hereinafter referred to as "sulfate ester group-introduced pulp"); The composition is characterized by exhibiting at least one function selected from the group consisting of deodorizing, antibacterial and antifungal properties. Effect of the Invention
[0007] The pulp in the functional material of the present invention is capable of supporting metal ions other than alkali metal ions without the intervention of inorganic porous crystals or the like, since at least a portion of the hydroxyl groups of the cellulose is substituted with sulfate ester groups. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing an example of a method for making a sulfate ester group-introduced pulp support metal ions. [Diagram 2] FIG. 2 is a schematic diagram illustrating a presumed mechanism by which metal ions other than alkali metal ions are supported on the pulp having ester sulfate groups introduced therein. [Diagram 3] FIG. 3 is a graph showing a calibration curve of absorbance corresponding to a range of metal ion concentrations (ppm (mg / L)) prepared using metal ion standard solutions. [Figure 4] FIG. 4 is a graph showing the relationship between metal ion concentration (ppm (mg / L)) and metal ion support amount (mmol / g) in the examples. [Diagram 5] Fig. 5(A) is a graph showing the relationship between the amount of sulfate ester groups (mmol / g) introduced into sulfate ester group-introduced pulp in the examples and the maximum amount of Cu2+ (copper (II) ion) supported (mmol / g). Fig. 5(B) is a graph showing the relationship between the amount of sulfate ester groups (mmol / g) introduced into sulfate ester group-introduced pulp in the examples and the molar ratio of sulfate ester groups to Cu2+. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The metal ion-supported pulp in the functional material of the present invention is a pulp having sulfate ester groups introduced therein and metal ions other than alkali metal ions are supported thereon.
[0010] The sulfate ester group-introduced pulp is a fibrous member formed by the assembly of a plurality of cellulose fibers, in which at least a portion of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer in which D-glucose is linked via β(1→4) glycosidic bonds) constituting the cellulose fibers contained therein have been substituted with sulfate ester groups represented by formula (1).
[0011] (-OSO3 - ) r Z r+ (1) In formula (1), r is an independent natural number from 1 to 7, Z r+ When r=1, it is at least one selected from the group consisting of a hydrogen ion, an alkali metal ion, a monovalent transition metal ion, an ammonium ion, an aliphatic ammonium ion, an aromatic ammonium ion, and a cationic polymer, and when r=2 or more, it is at least one selected from the group consisting of an alkaline earth metal ion, a polyvalent metal ion, and a compound containing two or more cationic functional groups (e.g., diamine, etc.) in the molecule.
[0012] In the formula (1), particularly when r is 2 or more, the sulfate ester group-introduced pulp may contain metal ions other than alkali metal ions. However, in the sulfate ester group-introduced pulp prepared by the method described below, r is often 1, and Z r+ is an alkali metal ion such as a sodium ion. The monovalent anion portion in formula (1) can also be referred to as a sulfate ester group.
[0013] <Physical properties of sulfate ester group-introduced pulp> The physical properties of the sulfate ester group-introduced pulp are not particularly limited, but are, for example, as follows.
[0014] <Amount of sulfate ester group introduced> The amount of sulfate ester groups introduced per 1 g (solid mass) of sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.6 mmol / g or more, 0.8 mmol / g or more, 1 mmol / g or more, or 1.2 mmol / g or more.
[0015] Incidentally, the upper limit is not particularly limited, but from the viewpoint of suppressing fiber collapse and cost increase caused by decreased crystallinity, for example, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 9.9 mmol / g or less, 5 mmol / g or less.
[0016] <Method for measuring the amount of sulfate ester groups introduced> The amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp can be evaluated based on the amount of sulfur introduced due to the sulfate ester groups, or by directly measuring the sulfate ester groups. For example, the amount of sulfate ester groups introduced into the pulp can be measured using a CHNS / O elemental analyzer. The amount of sulfate ester groups introduced into the pulp can also be calculated by measuring electrical conductivity.
[0017] <Crystallization degree> The sulfate ester group-introduced pulp may have, for example, a cellulose I type crystal structure as a crystal structure, and the degree of crystallinity may be 75% or less. From the viewpoint of maintaining the fiber shape, the degree of crystallinity of the sulfate ester group-introduced pulp is preferably 30% or more. Furthermore, from the viewpoint of handling in the preparation of the sulfate ester group-introduced pulp, the degree of crystallinity of the sulfate ester group-introduced pulp is, for example, 30% or more, 40% or more.
[0018] <Method for measuring crystallinity> The crystallinity of the sulfate ester group-introduced pulp can be measured, for example, by using an X-ray diffraction device.
[0019] <Average fiber length> The average fiber length of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 0.2 mm to 2 mm, 0.2 mm to 1.8 mm, 0.2 mm to 1.5 mm, or 0.2 mm to 1 mm.
[0020] <Short fiber length (%)> The sulfate ester group-introduced pulp may also contain pulp with short fiber length as described below. Examples of this pulp with short fiber length (hereinafter referred to as "short fiber") include pulp with a fiber length of 0.04 mm or more and 0.2 mm or less in the fiber length distribution. The content (%) of short fibers in the sulfate ester group-introduced pulp (i.e., short fiber rate (%)) is, for example, 10% or more, 15% or more.
[0021] From the viewpoint of handleability, the sulfate ester group-introduced pulp has a short fiber content (%) (i.e., short fiber rate (%)) of, for example, 10% to 70%, 10% to 60%, 10% to 50%, 10% to 45%, or 15% to 45% in terms of fiber length distribution.
[0022] <Average fiber width> The average fiber width of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 5 μm to 10 μm, 10 μm to 50 μm, 20 μm to 40 μm, or 20 μm to 30 μm.
[0023] <Measuring methods for average fiber length, average fiber width and fiber distribution> The average fiber length and average fiber width of the sulfate ester group-introduced pulp can be measured, for example, using a fiber tester or fiber length distribution measuring instrument manufactured by Lorentzen & Wettley in accordance with ISO 16065-2: 2007. The fiber length distribution and fiber width distribution of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring instrument in accordance with ISO 16065-2: 2007.
[0024] <Viscosity> When the degree of crystallinity of the sulfate ester group-introduced pulp is equal to or less than the aforementioned value, for example, the dispersion has a predetermined viscosity. For example, when the degree of crystallinity of the sulfate ester group-introduced pulp is 70% or less, the viscosity of the dispersion in which the sulfate ester group-introduced pulp is dispersed in water is 1000 mPa·s or more, 5000 mPa·s or more, or 10000 mPa·s or more. In particular, when the degree of crystallinity of the sulfate ester group-introduced pulp is 60% or less, the viscosity of the dispersion tends to increase. Furthermore, when the average fiber length is 1 mm or less, this tendency becomes stronger.
[0025] <Method of measuring viscosity> The viscosity (mPa s) of the sulfate ester group-introduced pulp can be measured, for example, using a B-type viscometer at a measurement temperature of 20°C, with the measurement being performed at rotation speeds of 6 rpm and 60 rpm. The thixotropy index (TI) value can also be calculated from each viscosity value. TI value = (viscosity at 6 rpm) / (viscosity at 60 rpm)
[0026] The TI value can be adjusted as appropriate, and when a high TI value is required, the lower limit of the TI value is, for example, 3 or more, 4 or more, or 5 or more. The upper limit of the TI value is, for example, 10 or less, 8 or less, 6 or less, or 5 or less. On the other hand, when a low TI value is preferred, the lower limit is, for example, 1 or more, and the upper limit is, for example, 3 or less, or 2.5 or less.
[0027] The sulfate ester group-introduced pulp can be obtained, for example, by the method shown below, but is not limited to this method.
[0028] In summary, this method involves subjecting a cellulose-containing fiber raw material (such as wood-based pulp (hereinafter simply referred to as "wood pulp")) to a chemical treatment to prepare sulfate ester group-introduced pulp. This chemical treatment process includes a contacting step in which the fiber raw material is contacted with a sulfate ester group-donor compound (described below) and urea or a urea derivative (hereinafter referred to as "urea, etc."), and a reaction step in which the fiber raw material after this contacting step is subjected to a heating reaction to substitute some of the hydroxyl groups of the cellulose with sulfate ester groups.
[0029] In this specification, the fiber raw material refers to fibrous pulp containing cellulose molecules. Pulp is a fibrous member in which a plurality of cellulose fibers are assembled. The cellulose fiber is an assembly of a plurality of fine fibers (for example, microfibrils, etc.). The fine fiber is an assembly of a plurality of cellulose molecules (hereinafter, sometimes simply referred to as "cellulose"), which are chain-like polymers in which D-glucose is bonded by β(1→4) glucoside. In addition, it is preferable to wash the fiber raw material in advance. For example, by filtering and dehydrating the material using water on a 200 mesh or 235 mesh sieve, it is possible to sieve out fine fibers and debris that are too fine, which is desirable because it improves the handling during preparation. In other words, pulp is an assembly of cellulose fibers that can become residues of 200 mesh or 235 mesh. The water may be tap water, but is preferably ion-exchanged water or pure water, and the same applies hereinafter.
[0030] The fiber raw material used in this method is not particularly limited as long as it contains cellulose as described above, and for example, what is generally called pulp may be used, or what contains cellulose isolated from sea squirts, seaweed, etc., and any material may be used as long as it is composed of cellulose molecules. Examples of the pulp include, but are not limited to, cotton-based pulps such as wood pulp, dissolving pulp, and cotton linter, non-wood-based pulps such as straw, bagasse, paper mulberry, mitsumata, hemp, kenaf, and fruit, and waste paper pulps prepared from recycled newspapers, magazines, cardboard, etc. Note that wood pulp is easy to use as a fiber raw material from the viewpoint of ease of availability.
[0031] There are various kinds of wood pulp, but the use is not particularly limited, and examples thereof include paper pulp such as softwood kraft pulp (NBKP), hardwood kraft pulp (LBKP), thermomechanical pulp (TMP), etc. When the pulp is used as a fiber raw material, one type of pulp may be used alone, or two or more types of pulp may be used in combination.
[0032] The sulfate ester group donating compound is not particularly limited as long as it is a compound capable of donating sulfate ester groups to fiber raw materials, and examples thereof include sulfamic acid, sulfamic acid salts, and sulfuryl compounds having a sulfonyl group with two oxygen atoms covalently bonded to sulfur, and these compounds may be used alone or in combination of two or more. The sulfate ester group donating compound is preferably sulfamic acid, since it has a lower acidity than sulfuric acid and has a higher efficiency of introducing sulfate ester groups, is inexpensive, and is highly safe. Hereinafter, an example will be described in which sulfamic acid is used as the sulfate ester group donating compound and urea is used as the urea.
[0033] <Contact process> The contact step is a step of contacting a fiber raw material containing cellulose with sulfamic acid and urea. This contact step is not particularly limited as long as it is a method that can cause the contact. For example, the fiber raw material may be immersed in a reaction solution in which sulfamic acid and urea are dissolved in a solvent to impregnate the fiber raw material with the reaction solution, or the reaction solution may be applied to the fiber raw material, or sulfamic acid and urea may be separately applied to, impregnated into, or sprayed onto the fiber raw material. Among these, if a method of immersing the fiber raw material in the reaction solution to impregnate the fiber raw material with the reaction solution is used, sulfamic acid and urea can be contacted uniformly with the fiber raw material.
[0034] The solvent for dissolving sulfamic acid and urea is not particularly limited, and examples thereof include protic polar solvents such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, and aqueous ammonia, aprotic polar solvents such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), and dimethylacetamide (DMA), and non-polar solvents such as diethyl ether, benzene, toluene, hexane, chloroform, and 1,4-dioxane. The solvent may be used alone or in combination of two or more. In particular, water is preferred from the viewpoint of easily dissolving sulfamic acid and urea.
[0035] In addition, the fiber raw material that has been brought into contact with sulfamic acid and urea through this contacting step is sometimes called "reaction liquid-impregnated fiber."
[0036] <Contact amount of reaction solution> In contacting the fiber raw material with the reaction solution, it is preferable to make the sulfamic acid and urea in the reaction solution have a predetermined ratio relative to the fiber raw material. Specifically, the reaction solution is contacted so that the amount of sulfamic acid and the amount of urea in the reaction solution are appropriate relative to the fiber raw material in the reaction solution-impregnated fiber when it is subjected to the reaction step. More specifically, the contact amount of sulfamic acid relative to the fiber raw material (solid mass, which is the dry mass) in the reaction solution-impregnated fiber immediately before being subjected to the heating reaction in the reaction step is adjusted to be equal to or greater than the contact amount of urea.
[0037] For example, the reaction liquid is prepared so that the mixing ratio of sulfamic acid and urea, in terms of mass ratio, is such that the value obtained by dividing the mass parts of sulfamic acid per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction by the mass parts of urea per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction (sulfamic acid / urea) is 0.8 or more, 0.85 or more, or 1 or more.
[0038] Also, for example, the contact amount of sulfamic acid is adjusted to be 70 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more per 100 parts by mass of the solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction.
[0039] For example, the contact amount of urea, i.e., the contact amount of urea relative to the mass of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction, is adjusted to 20 parts by mass or more, 30 parts by mass or more, or 50 parts by mass or more relative to 100 parts by mass of solid content of the fiber raw material while maintaining the above-mentioned relationship with sulfamic acid. The upper limit of the contact amount of urea is not particularly limited, but is, for example, 350 parts by mass or less, 300 parts by mass or less, or 250 parts by mass or less relative to 100 parts by mass of solid content of the fiber raw material.
[0040] The contact amounts of sulfamic acid and urea per 100 parts by mass of the solid content of the fiber raw material can be appropriately calculated depending on, for example, the state of the reaction liquid-impregnated fiber to be subjected to the reaction step.
[0041] <State of fiber impregnated with reaction liquid> The state of the reaction liquid-impregnated fiber to be subjected to the above-mentioned next reaction step may be, for example, the reaction liquid-impregnated fiber as it is, i.e., a state in which the fiber raw material is in contact with the reaction liquid without actively removing water, or a state in which the fiber raw material is in contact with the reaction liquid and the water has been actively removed, etc.
[0042] The former reaction liquid-impregnated fibers (in a state where water is not actively removed) include fibers in a state where the fiber raw material is in contact with the reaction liquid (including, for example, a slurry state, etc.), and fibers prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and leaving it to stand.
[0043] On the other hand, the latter reaction liquid-impregnated fiber (in a state where moisture has been actively removed) refers to a fiber in which moisture has been intentionally removed from a state where the fiber raw material is in contact with the reaction liquid. For example, it includes a fiber prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and naturally drying it by air drying or the like, a fiber prepared by filtering and dehydrating the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material, a fiber prepared by further air drying the filtered and dehydrated material, a fiber prepared by further drying the filtered and dehydrated material using a circulating air dryer, a fiber prepared by further drying the filtered and dehydrated material using a heating dryer, a fiber prepared by drying the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material using a circulating air dryer or a heating dryer, and the like.
[0044] In this way, the reaction liquid-impregnated fiber to be subjected to the reaction step may be one that has not been subjected to the active water removal as described above, or one that has been actively removed to remove a certain amount of water. In addition, when removing water by drying, there is no particular problem even if the moisture content after drying is about 1%. In particular, by using the latter method, the moisture content in the reaction liquid-impregnated fiber to be subjected to the reaction step can be reduced, so that the reaction time in the heating reaction in the reaction step can be shortened. This has the advantage of improving the productivity of the sulfate ester group-introduced pulp. In addition, by using the method of performing a dehydration treatment, there is the advantage that the reaction liquid-impregnated fiber can be prepared more efficiently than when a large amount of reaction liquid is treated.
[0045] When an active drying method is used, the moisture content of the reaction solution-impregnated fibers may be reduced to about 1%, or the moisture may be removed by drying the fibers to an absolutely dry state with a moisture content significantly lower than 1%.
[0046] In this specification, the term "wet state" refers to a fiber that is impregnated with the reaction liquid and has a moisture content of 1% or more, and is not in an absolute dry state. For example, the term "wet state" may refer to fibers that are impregnated with the reaction liquid, fibers that have been dehydrated to a certain extent, and fibers that have been dried to a certain extent.
[0047] In addition, in this specification, bone dry means a state in which the moisture content is reduced to less than 1% by, for example, reducing the pressure in a desiccator containing a desiccant such as calcium chloride or diphosphorus pentoxide, or by subjecting the material to a long-term heat drying treatment.
[0048] Therefore, when the latter method described above (a reaction method in a state where active moisture removal has been performed) is used in the contact step, a method for bringing the moisture content of the reaction liquid-impregnated fiber to a non-absolutely dry state may be used, or a method for bringing the moisture content to an absolute dry state may be used, but it is preferable to use a method for bringing the moisture content to a non-absolutely dry state.
[0049] In this specification, the moisture content of the reaction liquid-impregnated fiber is calculated using the following formula. Moisture content of reaction liquid-impregnated fiber (%) = 100 - (mass of solids in reaction liquid-impregnated fiber (g) / reaction liquid-impregnated fiber at the time of moisture content measurement (g)) x 100 = {(reaction liquid-impregnated fiber at the time of moisture content measurement (g) - solids in reaction liquid-impregnated fiber (g)) / reaction liquid-impregnated fiber at the time of moisture content measurement (g)} x 100
[0050] The solid content mass (g) in the reaction liquid-impregnated fiber in the above formula refers to the dry mass of the reaction liquid-impregnated fiber. Specifically, it refers to the dry mass adjusted to a constant weight by drying the sample at 105°C using a dryer or the like. For example, by putting the reaction liquid-impregnated fiber in a dryer and drying it under a specified drying condition (for example, a temperature of 105°C for 2 hours) and measuring the mass, the mass of the dried product after moisture has been removed from the reaction liquid-impregnated fiber (i.e., the mass of the product that is not removed under the drying condition. For example, the mass of the product containing the fiber raw material and the reagent in the reaction liquid) can be calculated. In addition, the constant weight means a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to enter or leave the facility. Specifically, it means a state in which the change in the mass between two consecutive measurements after drying for a certain period of time (for example, 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be at least half the drying time required for the first measurement).
[0051] The state of the fiber raw material when it is brought into contact with the reaction liquid is not particularly limited, and may be, for example, in a dry state or a wet state (i.e., a moist state).
[0052] <Pre-drying process in the contact process> In the above example, the method for preparing the reaction liquid-impregnated fiber in the contact step was described, in which the reaction liquid-impregnated fiber is prepared by actively removing water. When using a method for removing water while heating (pre-drying step) in this method (for example, when directly heating and drying the fiber raw material in the contact state with the reaction liquid, or heating and drying the dehydrated fiber), it is desirable to adjust the heating temperature to a predetermined temperature or lower. The drying temperature in this pre-drying step is not particularly limited, but is preferably adjusted to a temperature at which the water contained in the reaction liquid-impregnated fiber and the surrounding water can be removed and the reaction does not proceed. For example, the drying temperature in the pre-drying step can be adjusted so that the ambient temperature of the reaction liquid-impregnated fiber is 100°C or lower. On the other hand, from the viewpoint of workability, it is preferable to adjust the temperature to 50°C or higher. Therefore, the drying temperature in the pre-drying step in the contact step is preferably 50°C to 100°C, 70°C to 100°C.
[0053] <Moisture adjustment process during contact process> The contact step may include a moisture adjustment step in which the moisture content of the fiber raw material to be contacted with the reaction liquid is adjusted to fall within a predetermined range. This moisture adjustment step is a step in which the fiber raw material is dried or humidified to have a predetermined moisture content. By including this moisture adjustment step, the moisture content in the fiber raw material when it is contacted with the reaction liquid or the like can be made somewhat uniform, which may improve product stability in continuous operation. In addition, there is an advantage in that storage properties can be improved by drying the fiber raw material to a certain extent to reduce the moisture content (for example, the moisture content is 1% to 10%).
[0054] <Reaction process> As described above, the reaction liquid-impregnated fiber prepared in the contact step is subjected to the next reaction step. This reaction step is a step in which the cellulose fiber contained in the fiber raw material in the reaction liquid-impregnated fiber provided from the contact step is reacted with sulfamic acid and urea to replace at least a part of the hydroxyl groups in the cellulose fiber with sulfate ester groups of sulfamic acid, thereby introducing sulfate ester groups into the cellulose fiber contained in the fiber raw material. That is, this reaction step is a step in which a reaction is carried out to replace at least a part of the hydroxyl groups in the cellulose fiber contained in the reaction liquid-impregnated fiber with sulfate ester groups.
[0055] This reaction step is not particularly limited as long as it is a method capable of replacing at least a part of the hydroxyl groups of the cellulose fibers in the reaction solution-impregnated fibers with sulfate ester groups, and for example, a method of promoting the reaction by heating the reaction solution-impregnated fibers can be used. Hereinafter, the reaction will be described by taking the case where the reaction is carried out by this heating method as an example.
[0056] <Reaction temperature in the reaction process> The reaction temperature in the reaction step is not particularly limited, but is preferably a temperature at which sulfate ester groups can be introduced into the cellulose fibers constituting the fiber raw material while suppressing thermal decomposition and hydrolysis of the fibers. For example, the atmospheric temperature of the reaction liquid-impregnated fibers subjected to the reaction step is adjusted to 100°C to 200°C, 120°C to 200°C, 120°C to 180°C, or 120°C to 160°C. If the atmospheric temperature during heating is 200°C or less, thermal decomposition and discoloration of the fibers can be suppressed.
[0057] The heater or the like used in the reaction step is not particularly limited, and may be, for example, one capable of directly or indirectly heating the reaction liquid-impregnated fiber after the contact step while satisfying the above-mentioned requirements, and may be a known dryer, reduced pressure dryer, microwave heating device, autoclave, infrared heating device, hot pressing method using a heat press machine (e.g., AH-2003C manufactured by AS ONE Co., Ltd.), etc. In particular, from the viewpoint of operability, it is preferable to use a circulating air dryer since gas may be generated in the reaction step.
[0058] <Reaction time in the reaction process> The heating time (i.e., reaction time) when the heating method is used as the reaction step is not particularly limited, but is, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, or 15 minutes or more when the reaction temperature is adjusted to be within the above range, and from the viewpoints of operability and cost, it is 5 minutes to 300 minutes, or 5 minutes to 120 minutes.
[0059] By carrying out the above steps, a pulp having sulfate ester groups introduced therein can be prepared.
[0060] <Cleaning process after reaction process> The reaction step may be followed by a washing step in which the sulfate ester group-introduced pulp is washed. The sulfate ester group-introduced pulp has an acidic surface due to the effect of sulfamic acid (sulfate ester group-donating compound). In addition, unreacted reaction liquid is still present. For this reason, if a washing step is provided in which the reaction is completely terminated and excess reaction liquid is removed to make the pulp neutral, the handling properties can be improved.
[0061] This washing step is not particularly limited, and may be any step that can make the sulfate ester group-introduced pulp nearly neutral. For example, a method of washing the sulfate ester group-introduced pulp with pure water or the like until it becomes neutral may be used. Neutralization washing may also be performed using an alkaline solution or the like. When performing such neutralization washing, examples of the alkaline compound contained in the alkaline solution include inorganic alkaline compounds and organic alkaline compounds. Examples of the inorganic alkaline compounds include hydroxides, carbonates, and phosphates of alkali metals. Examples of the organic alkaline compounds include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and hydroxides of heterocyclic compounds.
[0062] The method for separating the sulfate ester group-introduced pulp in the washing step is not particularly limited, and may be, for example, by filtering the sulfate ester group-introduced pulp and the washing water. For example, the sulfate ester group-introduced pulp after the reaction may be washed using a stainless steel sieve with an opening size of 243 μm (70 mesh) to 20 μm (635 mesh), 132 μm (120 mesh) to 45 μm (300 mesh), or 75 μm (200 mesh) to 45 μm (300 mesh).
[0063] Examples of metal ions other than the alkali metal ions (hereinafter, simply referred to as "metal ions") include copper ions, zinc ions, silver ions, gold ions, platinum ions, nickel ions, manganese ions, iron ions, cobalt ions, magnesium ions, aluminum ions, calcium ions, chromium ions, tin ions, barium ions, and lead ions.
[0064] Next, an example of a method for making the sulfate ester group-introduced pulp support metal ions will be described with reference to FIG. 1, but the method is not limited to this example.
[0065] 1, an aqueous solution of metal ions 2 is placed in a container 3 with a lid, and then a sulfate ester group-introduced pulp 1 is submerged in the aqueous solution of metal ions 2, and the container 3 is then covered with a lid, and the sulfate ester group-introduced pulp 1 is immersed in the aqueous solution of metal ions 2 for a predetermined period of time. After the immersion, the sulfate ester group-introduced pulp 1 is washed with a large amount of water on a 200-mesh sieve, thereby obtaining a sulfate ester group-introduced pulp carrying metal ions (metal ion-carrying pulp in the present invention).
[0066] The concentration of metal ions in the aqueous solution of metal ions 2 is, for example, 100 ppm to 1000 ppm (100 mg / L to 1000 mg / L). By using an aqueous solution of metal ions 2 with a higher concentration, the time required for the metal ions to be supported on the sulfate ester group-introduced pulp can be shortened. On the other hand, it is expected that increasing the concentration of the aqueous solution of metal ions 2 will increase the amount of metal ions that are not supported on the sulfate ester group-introduced pulp, and considering the load during wastewater treatment, it is desirable to set the concentration of the aqueous solution of metal ions 2 to an appropriate level.
[0067] The ratio between the amount (volume) of the aqueous metal ion solution 2 and the mass of the sulfate ester group-introduced pulp 1 to be immersed therein is not particularly limited, but may be, for example, a ratio of about 0.5 g of sulfate ester group-introduced pulp 1 to 50 mL of the aqueous metal ion solution 2.
[0068] The time for which the sulfate ester group-introduced pulp 1 is immersed in the aqueous metal ion solution 2 is not particularly limited, and may be, for example, about 5 minutes or more.
[0069] Next, the assumed mechanism by which metal ions other than alkali metal ions are supported on the sulfate ester group-introduced pulp will be described with reference to Fig. 2. As shown in Fig. 2, in the aqueous metal ion solution 2 shown in Fig. 1, the alkali metal ions (Na + (sodium ion)) is a metal ion other than an alkali metal ion (Cu in Figure 2). 2+ It is presumed that metal ions other than alkali metal ions are supported on the sulfate ester group-introduced pulp by, for example, exchanging with cations of alkali metal ions. However, the present invention is not limited to this presumption. The metal ions other than alkali metal ions supported on the sulfate ester group-introduced pulp may be of one type or two or more types.
[0070] It will be demonstrated in the examples described later that the sulfate ester group-introduced pulp can support metal ions other than alkali metal ions, and that the metal ions are supported in the maximum amount on the sulfate ester group-introduced pulp.
[0071] The functional material containing the metal ion-supported pulp of the present invention can exhibit one or more of the following functions: deodorizing, antibacterial, and antifungal. The aforementioned Patent Document 1 (Patent No. 4149066) describes that metal ions other than alkali metal ions exhibit deodorizing and antibacterial functions, and the website of the patent holder of this patent publication (Rengo Co., Ltd.) additionally describes that metal ions other than alkali metal ions exhibit antifungal functions. (https: / / www.rengo.co.jp / products / functional / cellg.html). In addition, the fact that metal ions other than alkali metal ions exhibit deodorizing functions is also described in Toa Gosei Research Annual Report No. 3 52-56 (2000) and Ehime Prefectural Industrial Technology Research Institute Research Report No. 54 6-10 (2016). And, the fact that metal ions other than alkali metal ions exhibit antibacterial functions is also described in the Japanese Journal of Home Economics Vol. 53 No. 9 927-935 (2002). Furthermore, the fact that metal ions other than alkali metal ions exhibit antibacterial and antifungal effects is also described in the September 2008 issue of Aisanken Food Industry Technology Center News (https: / / www.aichi-inst.jp / shokuhin / other / shokuhin_news / s_no34_2_01.pdf). EXAMPLES
[0072] (Preparation of sulfate ester group-introduced pulp) Softwood kraft pulp (NBKP) with an average fiber length of 2.54 mm (hereinafter, simply referred to as "pulp") manufactured by Marusumi Paper Co., Ltd. was washed with a large amount of ion-exchanged water, and then the water was drained using a sieve with an opening of 75 μm (200 mesh). The solid content of a part of the pulp thus obtained was measured, and it was found to be 21.6 mass%. The ion-exchanged water used had an electric conductivity of 0.1 μS / cm to 0.2 μS / cm measured using an ion-exchanged water generator (model number: G-5DSTSET) manufactured by Organo Co., Ltd., and is hereinafter referred to as pure water. The wet pulp was then spread on an aluminum pad, placed in a dryer under an atmosphere of 105°C, and dried for about 1 hour until the moisture content reached about 1%.
[0073] <Contact process> 1000 g of the reaction solution was added to 20 g of pulp (solid content mass), and the reaction solution was impregnated into the pulp. The reaction solution used was an aqueous solution in which sulfamic acid and urea were mixed in a concentration ratio (g / L) of sulfamic acid:urea=200 g / L:400 g / L. The sulfamic acid used was a product of Fuso Chemical Co., Ltd. with a purity of 99.8%, and the urea used was a product of Fujifilm Wako Pure Chemical Co., Ltd. with a purity of 99.0%, model number: special grade reagent.
[0074] The pulp impregnated with the reaction solution was dehydrated by suction filtration and spread on an aluminum tray. The aluminum tray was then placed in a dryer at 80°C to dry, preparing a pulp impregnated with the reaction solution. Filter paper (manufactured by Advantech, model number: No. 2) was used for the suction filtration.
[0075] <Reaction process> The reaction solution-impregnated pulp was subjected to a heating reaction using a dryer, the temperature of the thermostatic chamber of the dryer was set to 120° C., and the heating time was set to 25 minutes.
[0076] <Cleaning process after reaction process> The pulp after the reaction step was neutralized on a sieve with an opening of 45 μm (300 mesh) and then washed with pure water. An aqueous solution of sodium bicarbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used as the neutralizing agent. In this way, sulfate ester group-introduced pulp with an introduction amount of sulfate ester group of 0.68 mmol / g was prepared.
[0077] (Metal ion support) As shown in Figure 1, metal ions (Cu, 2+ or Zn 2+ 0.5 g of sulfate ester group-introduced pulp was submerged in 50 mL of an aqueous solution of zinc (II) ion) and soaked for 5 minutes. The aqueous solution of metal ions was prepared by dissolving metal chloride (copper (II) chloride dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) or zinc (II) chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)) in pure water, and the concentration indicates the metal ion concentration in the dissolved metal chloride. After the soaking, the sulfate ester group-introduced pulp was washed with a large amount of pure water on a 200 mesh sieve to obtain sulfate ester group-introduced pulp (metal ion-loaded pulp) loaded with metal ions.
[0078] 3 is a graph showing a calibration curve used for quantifying the amount of supported metal ions from the concentration of the aqueous solution of the metal ions. A metal standard solution (1000 ppm (1000 mg / L) copper standard solution (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., model number: JCSS element standard solution) or 1000 ppm (1000 mg / L) zinc standard solution (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., model number: JCSS element standard solution)) was used for creating the calibration curve. These standard solutions were diluted with 0.1 M acetate buffer at pH 5.5 to prepare diluted standard solutions (aqueous solutions of metal ions) of 0.2 ppm (0.2 mg / L), 0.5 ppm (0.5 mg / L), 0.7 ppm (0.7 mg / L) and 1 ppm (1 mg / L). 10 μL of 1.4 mM xylenol orange (metal indicator (coloring reagent)) was added to a quartz cell containing 2.5 mL of diluted standard solution, and the metal indicator (coloring reagent) was measured at 576 nm (Cu 2+ ) or 572 nm (Zn 2+The absorbance of Cu was measured. The reference solution (metal ion concentration 0 ppm) was the acetate buffer solution. 2+ The results are shown in Fig. 3(B). 2+ As shown in Figure 3, a good calibration curve was obtained at metal ion concentrations of 1 ppm (1 mg / L) or less.
[0079] Using the calibration curve, the amount of metal ions carried by the metal ion-loaded pulp was quantified. The aqueous solution of metal ions used in the preparation of the metal ion-loaded pulp described above was diluted with 0.1 M acetate buffer at pH 5.5 to about 0.5 ppm (about 0.5 mg / L), which is within the range of the calibration curve. In this case, the supernatant of the aqueous solution of metal ions after centrifugation was collected to prevent contamination with pulp.
[0080] The absorbance of the diluted solution was measured in the same manner as in the preparation of the calibration curve described above, and the amount of metal ion supported was calculated from the difference in concentration of the aqueous metal ion solution before and after the addition of the sulfate ester group-introduced pulp, using the absorbance and the calibration curve.
[0081] For example, if the concentration of the metal ion in the aqueous solution (50 mL) before the addition of sulfate ester group-introduced pulp (0.5 g) is 100 ppm (100 mg / L) and the concentration after the addition is 90 ppm (90 mg / L), it is understood that 500 μg of metal ion can be supported. In other words, 1 mg of metal ion is supported per 1 g of sulfate ester group-introduced pulp.
[0082] FIG. 4 is a graph showing the relationship between the metal ion concentration (100 ppm (100 mg / L), 200 ppm (200 mg / L), 500 ppm (500 mg / L) and 1000 ppm (1000 mg / L)) in the aqueous solution of the metal ions and the amount of metal ions (mmol / g) in sulfate ester group-introduced pulp with an introduction amount of sulfate ester groups of 0.68 mmol / g. 2+ The results are shown in Fig. 4(B). 2+As shown in Fig. 4, as the metal ion concentration increases, the amount of supported metal ions reaches a certain value (hereinafter, this is referred to as the "maximum supported amount"), and it was found that the sulfate ester group-introduced pulp is capable of supporting metal ions.
[0083] Figure 5(A) shows the relationship between the amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp (mmol / g) and Cu 2+ FIG. 5(B) is a graph showing the relationship between the amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp (mmol / g) and the maximum amount of Cu supported (mmol / g). 2+ 5 is a graph showing the relationship between the molar ratio of sulfate ester group and the amount of sulfate ester group introduced. In Fig. 5(A) and Fig. 5(B), the sulfate ester group refers to the monovalent anion moiety in the above formula (1). The sulfate ester group-introduced pulps in Fig. 5 having the amounts of sulfate ester group introduced of 1.02 mmol / g and 1.58 mmol / g were prepared in the same manner as the sulfate ester group-introduced pulp having the amount of sulfate ester group introduced of 0.68 mmol / g, except that in the above contact step, the ratios of sulfamic acid:urea were 200 g / L:300 g / L and 200 g / L:100 g / L. The sulfate ester group-introduced pulp in FIG. 5, in which the amount of sulfate ester groups introduced is 1.88 mmol / g, was prepared in the same manner as the sulfate ester group-introduced pulp in which the amount of sulfate ester groups introduced is 0.68 mmol / g, except that in the contact step, 100 g of reaction solution was added to 5 g of pulp (solid content mass) and the ratio of sulfamic acid to urea was 200 g / L:100 g / L. As shown in FIG. 5(A) and FIG. 5(B), the sulfate ester groups and Cu 2+ The ratio of Cu to sulfate ester group-introduced pulp was approximately 1:0.5. 2+ It was confirmed that the maximum amount was supported.
[0084] (Deodorizing performance evaluation) 2 L of acetic acid gas at 40 ppm was sealed in a 5 L PVDF (polyvinylidene fluoride) pack with a cock, and 0.35 mmol / g Cu was added to the sulfate ester group-introduced pulp with 0.68 mmol / g of sulfate ester group.2+ 0.5 g of metal ion-loaded pulp with a moisture content of less than 10% was placed in the container, and the container was left to stand for 2 hours at room temperature (20-25°C). The acetic acid gas concentration was measured before and after the container was placed in the container using the detector tube method (a gas detector tube attached to a gas sampler is used to draw in 100 mL of the gas to be measured, and the concentration was visually read from the detector tube scale). The acetic acid gas removal rate was 97.5%. An acetic acid gas detector tube (manufactured by Gastec Corporation, measurement range 1 ppm-100 ppm) was used as the detector tube. On the other hand, Cu 2+ Instead, Na + When measurements were taken under the same conditions, except that sulfate ester group-introduced pulp carrying Cu was used, the acetic acid gas removal rate was about 40%. When measurements were taken under the same conditions, except that softwood kraft pulp (NBKP) without sulfate ester group was used, the acetic acid gas removal rate was about 10%. 2+ It was confirmed that the sulfate ester group-introduced pulp carrying the ester exhibited an excellent deodorizing effect against the odor caused by acetic acid gas.
[0085] (Antibacterial performance evaluation) The antibacterial performance was evaluated by the bacterial liquid absorption method in accordance with JIS L 1902. Staphylococcus aureus NBRC 12732 was used as the test bacterial strain for the evaluation. The test bacterial suspension was prepared by adding a surfactant (Tween 80 (registered trademark)). The evaluation sample was a sulfate ester group-introduced pulp with an introduction amount of 0.68 mmol / g of sulfate ester groups and a 0.35 mmol / g Cu solution. 2+ The metal ion-loaded pulp and softwood kraft pulp (NBKP) without sulfate ester groups were freeze-dried to a moisture content of less than 10%. In addition, a control sample was cultured using a standard cloth (100% cotton, white cloth) instead of the evaluation sample.
[0086] The antibacterial activity value was calculated according to the following formula using the viable cell counts obtained in the test immediately after inoculation and after 18 hours of culture. Antibacterial activity value = {(common logarithm of the number of viable bacteria in the control sample after 18 hours of culture) - (common logarithm of the number of viable bacteria in the control sample immediately after inoculation)} - {(common logarithm of the number of viable bacteria in the evaluation sample after 18 hours of culture) - (common logarithm of the number of viable bacteria in the evaluation sample immediately after inoculation)} = (growth value F of the control sample) - (growth value G of the evaluation sample) *However, when (common logarithm of the viable bacterial count in the control sample immediately after inoculation) > (common logarithm of the viable bacterial count in the evaluation sample immediately after inoculation), (common logarithm of the viable bacterial count in the evaluation sample immediately after inoculation) is replaced with (common logarithm of the viable bacterial count in the control sample immediately after inoculation) to calculate the antibacterial activity value.
[0087] As a result of the test, Cu 2+ The antibacterial activity of the metal ion-loaded pulp was 5.9, and that of softwood kraft pulp (NBKP) was 1.2. 2+ It was confirmed that the sulfate ester group-introduced pulp carrying the cellulose exhibited excellent antibacterial effects against bacterial strains.
[0088] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention. [Explanation of symbols]
[0089] 1. Sulfate ester group-introduced pulp 2. Aqueous solutions of metal ions 3. Container with lid
Claims
1. The present invention includes a metal ion-supported pulp in which at least a portion of the hydroxyl groups of cellulose is substituted with sulfate ester groups and a metal ion other than an alkali metal ion is supported on the pulp, A functional material characterized by exhibiting at least one function selected from the group consisting of deodorizing, antibacterial and antifungal properties.
2. 2. The functional material according to claim 1, wherein the metal ion other than the alkali metal ion is at least one selected from the group consisting of copper ions, zinc ions, silver ions, gold ions, platinum ions, nickel ions, manganese ions, iron ions, cobalt ions, magnesium ions, aluminum ions, calcium ions, chromium ions, tin ions, barium ions and lead ions.
Citation Information
Patent Citations
Fabrics, nonwovens, or papers containing inorganic porous crystal-hydrophilic polymer composites
JP4149066B2